Neutron imaging and molecular simulation of systems from methane and p-xylene - Martin Melčák; Tereza-Markéta Durďáková; Štěpán Tvrdý; Jonatan Šercl; Jong Min Lee; Pierre Boillat; Jan Heyda; Pavel Trtik; Ondřej Vopička (Scientific Reports)
Abstract Bulk properties of two-phase systems comprising methane and liquid p-xylene were derived experimentally using neutron imaging and theoretically predicted using molecular dynamics (MD). The measured and predicted methane diffusivity in the liquid, Henry’s law constant, apparent molar volume, and surface tension compared well within the experimentally studied conditions (273.15 to 303.15 K, ≤ 100 bar). Since MD is a physical model, extrapolations of the two-phase systems properties were performed for a broader temperature range (260 to 400 K, ≤ 100 bar). Moreover, the species diffusivities in single phases formed by infinitely diluted p-xylene in methane were predicted under conditions relevant to the methane liquefaction (90 to 290 K, 50 bar). The predicted p-xylene diffusivity in the supercritical methane was one order of magnitude higher than that calculated using Wilke–Chang and He–Yu correlations. This study provides novel experimental and MD-simulated characteristics for this industrially relevant system, for which intensive freeze-out formation from the supercritical methane is predicted.